Preparación metodológica del docente en la educación inclusiva de estudiantes con abandono emocional de 2° a 4° de educación general básica - Gómez Caranqui, Shirley Patricia (2019)
The research presented addresses the problem of emotional abandonment in children from the 2nd to 4th EGB of the School of Basic Education "Zoila Rosa Garcia Montenegro" located in the Cantón Durán, province of Guayas. It is oriented in specificto the methodological preparation of the teacher to face these educational needs in the classroom. For the given problems, a descriptive and field research is presented, basically qualitative - quantitative, which identifies the aspects to be taken into account for the identification of emotional abandonment as part of the special educational need not associated with a disability and of the preparation Methodological Approach of Teachers to Address………..